Pliss Pomózcie!

Zapisz w postaci sum jednomianów:
a) (x+√3)(x-√3)
b) -2(a-√2)(a+√2)
c) -2(x+4)²-3(x-2)(x+2)
d) (x-2)(x+4)-2(2x+1)²
e) (2x-√5)²-2*(½x+√2)²

pilne! to na jutro:/
z góry dzięki:)


Odpowiedź :

a) (x+√3)(x-√3)=2x
b) -2(a-√2)(a+√2)=-2a+2√2+a+√2=-a+4
c) -2(x+4)²-3(x-2)(x+2)=-2x²-32-3x+2+x+2=-2x²-28-2x
d) (x-2)(x+4)-2(2x+1)²=x-2+x+4-8x²-2=2x-8x²
e) (2x-√5)²-2*(½x+√2)²=4x-√25-1/2x-4=3,5x-9
a) (x+√3)(x-√3)=x²-3
b) -2(a-√2)(a+√2)=-2(a²-2)=-2a²+4
c) -2(x+4)²-3(x-2)(x+2)=-2(x²+8x+16)-3(x²-4)=-2x²-18x-32-3x²+12=
=-5x²-18x-20
d) (x-2)(x+4)-2(2x+1)²=x²-16-2(4x²+4x+1)=x²-16-8x²-8x-2=-18-7x²-8x
e) (2x-√5)²-2*(½x+√2)²=4x²-4√5x+5-2(1/4x+√2+2)=4x²-4√5x+5-1/2x-2√2-4